Um esquema de equaliza??o turbo aplicando decodifica??o turbo de c?digos produto de paridade simples multidimensionais - Santos, Andr? Fonseca dos (2005)
Combining blocks existing in a different way, a new turbo equalization scheme is proposed in this work for fixed channels with multipath. Existing schemes in the joint turbo equalization literature turbo decoding iteration perform a complete turbo decoder at each iteration of the turbo equalizer. In the proposed scheme in this paper it is used only a decoder component a turbo code. Each iteration is performed equalization and decoding a dimension of a simple parity product code. Thus, it is not necessary to process all the dimensions of the product code on each iteration of the turbo equalizer. The results obtained by simulations show that for higher encoding rates, the performance of this scheme is superior to the turbo equalizers in the literature.